Maternal Anxiety Levels with Newborns in the Neonatal Intensive Care Unit at Hilla Maternity and Childbirth Hospital in AL-Hilla City - Abdulmahdi A. Hasan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims: To comparing maternal anxiety levels for infants in the NICU and mother in the postnatal care-service(PCS) for stable newborns. Methodology This descriptive study was carried out in Al-Hilla Children’s andBirth Hospital, Al-Hilla City . The 1st 200 families, counting pregnant mother in personal care services(n=100) and pregnant women in neonatal intensive care unit (n=100), backed up by participant as ofMay , 2018. As data gathering tools, including the STAI TX-1-STAI TX-2 inventory, questionnaires wereused to detect the characteristic of mother and newborn. Results Characteristic rates of anxiety were notsubstantially different between NICU neonate mothers and PCS neonate mothers (t = 0.588, p = 0.557),while status level of anxiety varied greatly among the 2 classes (t = -5.109, p = < 0.001). Motherland anxietylevel were determined to be higher for mother whose children in the NICU compared with those of motherwhose children were on personal care-services. Conclusion It can boost anxiety and lead to mothers beinga mother to a newborn sick. During this difficult time, nursing care may rise mothers’ ability to deal with thesick stresses of the newborn